PERENCANAAN DRAINASE YANG BERWAWASAN LINGKUNGAN PADA JALAN TOL SEMARANG – SOLO - Andhika Rhama Mahardika; Fahmi Anggriawan Yulianto; Suripin Suripin; Hari Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Semarang – Solo Toll Road is the fastest access between Semarang and Solo. This toll road have been operated gradually in phase I (passing through Penggaron, Gedawang, and Bergas region along 24,75 km) since 2011. The construction of this toll road lead to the change of land use and increased impermeable surface area so that rainfall can’t be absorbed into the soil and resulting in increased runoff flow and volume. Increment of the runoff flow and volume if not handled immediately will cause flood. To overcome this, the runoff flow that occurs at this time should be returned to the state before the Semarang – Solo toll road was made. Design of sustainable drainage system is used to decrease runoff flow that increased due to the development of the toll roads. The design of this sustainable drainage system is planned along the 8,475 km from phase I. Sustainable drainage system can be defined as an effort to manage the excess water by artificially percolate it into the ground or flow it into the river without exceeding the capacity of the river. The facilities that offered in this final task is to build infiltration wells in the drainage channels. To restore the flow and runoff volume to pre-construction conditions, it takes 5.682 pieces of infiltration wells. From the analysis and calculation result, the number of infiltration wells that can be installed are 2.581 pieces. That is equal to 45,42 % of the overall that required to overcome the effect of runoff flow of Semarang – Solo toll road development.